Progression of carotid vascular damage and cardiovascular events in non-alcoholic fatty liver disease patients compared to the general population during 10 years of follow-up - Fracanzani, A.; Tiraboschi, S.; Pisano, G.; Consonni, D.; Baragetti, A.; Bertelli, C.; Norata, Giuseppe; Valenti, L.; Grigore, L.; Porzio, M.; Catapano, A.; Fargion, S. (Elsevier Ireland, 2016)
© 2016 Elsevier Ireland Ltd. Background and aim: Non-alcoholic fatty liver disease (NAFLD) is associated not only with liver related morbidity and mortality but also with an increased risk of cardiovascular disease. Aim: to evaluate in patients with NAFLD and in matched Controls after 10 years of follow-up 1 the incidence of major cardiovascular and cerebral events 2 the progression of vascular damage. Methods: Clinical and cardio-metabolic data were collected in 125 NAFLD patients and 250 age and gender matched Controls at baseline and 10 years later. Incidence of cardiovascular and cerebral events was recorded. By ultrasonography, carotid intima-media thickness (cIMT), presence of plaques and presence of fatty liver were evaluated. Results: 25% of the overall series was lost to follow-up. Sixty-eight (37%) Controls developed steatosis. Major cardiovascular events were observed in thirty-five subjects (17/91 (19%) NAFLD and 18/182 (10%) Controls), with an estimated cumulative risk significantly higher in NAFLD than in Controls, log-rank test for equality of failure functions p = 0.007. At multivariate analysis, presence of plaques (hazard ratio 5.08 (95% C.I. 2.56-10.96) and of steatosis (hazard ratio 1.99 (1.01-3.94)) were the strongest predictors for cardiovascular events. Grade of steatosis, ALT and GGT levels were higher in NAFLD patients who developed cardiovascular events. cIMT value after 10 years was significantly higher in NAFLD than in Controls, but the mean progression rate was higher in Controls (0.015 and 0.006 mm/year, p = 0.001). In conclusion our results suggest that NAFLD has to be included among risk factors for cardiovascular damage and underline the utility to evaluate, once NAFLD is diagnosed, the presence of atherosclerotic lesions.